Magnetic core materials and magnetic cores

A magnetic core material with Fe-based soft magnetic powder and a blended epoxy resin addresses issues of permeability, frequency characteristics, and strength, ensuring effective performance and preventing resin blowout in induction heating devices.

JP7611775B2Active Publication Date: 2025-01-10NTN CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021095071
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-30
Filing Date
2021-06-07
Publication Date
2025-01-10
Estimated Expiration
2041-06-07

AI Technical Summary

Technical Problem

Existing powder magnetic cores for induction heating devices face challenges in achieving low magnetic permeability, good frequency characteristics, sufficient strength, and volume resistivity, especially at high frequencies, and are prone to resin blowout during thermosetting, leading to structural defects and decreased productivity.

Method used

A magnetic core material composed of Fe-based soft magnetic powder with an inorganic insulating coating and a specific blend of epoxy resin, including bisphenol A and novolac type epoxy resin, is used, with controlled particle size and alloy composition to achieve low magnetic permeability, improved frequency characteristics, and enhanced strength and resistivity, preventing resin blowout during curing.

Benefits of technology

The solution results in a magnetic core with low magnetic permeability, good frequency characteristics, and sufficient strength, while preventing resin blowout, thus improving productivity and maintaining desired properties in high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611775000001
    Figure 0007611775000001
  • Figure 0007611775000002
    Figure 0007611775000002
  • Figure 0007611775000003
    Figure 0007611775000003
Patent Text Reader

Abstract

To provide a magnetic core material capable of obtaining a magnetic core having good frequency characteristics and satisfying the required strength and volume resistivity, and capable of suppressing resin blowout during thermosetting while having low magnetic permeability.SOLUTION: A magnetic core material contains Fe-based soft magnetic powder having an inorganic insulating film 4b formed on the surface of Fe-based soft magnetic particles 4a, and an epoxy resin 4c containing a curing agent. The Fe-based soft magnetic particles 4a are formed of pure iron powder or low alloy steel powder. The content of the epoxy resin containing the curing agent is set to 2 to 5 mass%. The epoxy resin is a mixture of a bisphenol A type epoxy resin and a novolak type epoxy resin.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnetic core material and a magnetic core. [Background technology]

[0002] The magnetic core attached to the heating coil of the high-frequency hardening device has the effect of concentrating magnetic lines on the workpiece by attaching it to the back of the coil to increase power and promote induction heating, or conversely, shielding the magnetic lines by attaching it to the front of the coil to prevent heating of areas that do not need to be hardened, making it an essential part of the heating coil of the high-frequency hardening device. Dust cores manufactured by powder metallurgy have little raw material loss and are excellent for mass production, so they are widely used as magnetic cores for the heating coil of the high-frequency hardening device.

[0003] Patent Document 1 discloses a magnetic core for use in a high-frequency hardening device, which is made by mixing 97 wt% iron powder particles whose surfaces are covered with an inorganic insulating coating with 3 wt% epoxy resin powder containing dicyandiamide as a curing agent, removing particles that pass through a sieve with 106 μm openings but do not pass through a 25 μm sieve, heating and kneading this at 110° C. for 15 minutes, compression molding at a molding pressure of 200 MPa, and then heating at 180° C. for 1 hour in a nitrogen atmosphere to cure the epoxy resin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. WO2016 / 043295 Summary of the Invention [Problem to be solved by the invention]

[0005] Powder core-type magnetic cores for induction heating devices are used in the high frequency range of power supply frequencies from about 10 kHz to 500 kHz. It is necessary to select an appropriate frequency and relative permeability of the magnetic core according to the desired hardening depth. For example, at high frequencies of 100 kHz or more, depending on the hardening depth, it is often necessary to use a core with a relative permeability of less than 25, especially around 20.

[0006] In order to keep the relative permeability below 25, for typical powder magnetic cores that do not contain resin binders, it is necessary to reduce the molding pressure extremely and mold them to a low density. However, it is practically difficult to achieve a relative permeability of less than 25 within the moldable range, and even if it is possible to mold it, there will be many voids inside that will become structural defects, which will result in a problem of insufficient strength when used as a core for induction hardening. In addition, the volume resistivity will be low, which will increase eddy current loss, resulting in increased loss in the high frequency range and deterioration of frequency characteristics.

[0007] The magnetic cores used in induction hardening may become very hot depending on the conditions of use. When used at high temperatures, the lifespan of the magnetic core is shortened, so it is preferable to design the core to have a low temperature as much as possible. The main factors that cause the core to become very hot are radiant heat from the workpiece being hardened and heat generated by iron loss in the magnetic core itself. Heat generation from the magnetic core itself can be suppressed by selecting the material of the iron powder particles.

[0008] Furthermore, it has been found that in powder magnetic cores using a resin binder as in Patent Document 1, depending on the type of resin binder, the resin binder may erupt (eject) onto the surface when the resin is thermally cured. If the resin erupts in this way, the green bodies are bonded to plates that align them in the heating furnace for thermal curing, which can lead to reduced productivity.

[0009] The present invention has been made to address such problems, and aims to provide a magnetic core material that can obtain a magnetic core that has low magnetic permeability, good frequency characteristics, and satisfies the required strength and volume resistivity, and can suppress the blowing out of resin during thermal curing. [Means for solving the problem]

[0010] The magnetic core material according to the present invention contains an Fe-based soft magnetic powder in which an inorganic insulating coating is formed on the surface of Fe-based soft magnetic particles, and an epoxy resin material, the epoxy resin material being made of a hardener and an epoxy resin, the Fe-based soft magnetic particles being pure iron powder or low-alloy steel powder, the content of the epoxy resin material being 2 mass% or more and 5 mass% or less, and the epoxy resin being made of bisphenol A type epoxy resin and novolac type epoxy resin.

[0011] A magnetic core using the above magnetic core material can provide a magnetic core that has low magnetic permeability, good frequency characteristics, and satisfies the required radial crushing strength and volume resistivity.

[0012] When using low-alloy steel powder as the Fe-based soft magnetic particles, it is preferable that the low-alloy steel powder contains either or both of Si and Cr as alloying components, and the total content of the alloying components in the low-alloy steel powder is 6.5 mass or less, thereby achieving low magnetic permeability.

[0013] When pure iron powder is used as the Fe-based soft magnetic particles, the content of the epoxy resin material is preferably 3 mass % or more and 5 mass % or less.

[0014] The Fe-based soft magnetic powder preferably has a median diameter D50 of 10 μm or more and 70 μm or less, which can reduce iron loss in the magnetic core and suppress heat generation in the magnetic core itself.

[0015] The magnetic core can be formed by curing the epoxy resin of the magnetic core material described above.

[0016] The relative permeability of this magnetic core is preferably 17-25.

[0017] The radial crushing strength of this magnetic core is preferably 50 MPa or more.

[0018] The volume resistivity of this magnetic core is 1×10 4 Ωcm or more is preferable.

[0019] It is preferable that the inductance retention rate of this magnetic core at 1000 kHz relative to 5 kHz is 80% or more.

[0020] By combining the above magnetic core with a coil, it is possible to provide an induction heating device equipped with a high-strength magnetic core with a high degree of freedom in selecting the hardening depth, low loss, even in the high frequency range. Effect of the Invention

[0021] According to the present invention, it is possible to obtain a magnetic core having low magnetic permeability, good frequency characteristics, and the necessary strength and volume resistivity, and it is also possible to provide a magnetic core material that can suppress the blowing out of resin during thermal curing. [Brief description of the drawings]

[0022] [Figure 1] FIG. 2 is a diagram showing a schematic positional relationship between a magnetic core and a coil in an induction hardening device. [Diagram 2] FIG. 2 is a diagram showing a schematic positional relationship between a magnetic core and a coil in an induction hardening device. [Diagram 3] FIG. 2 is a cross-sectional view of a particle of the composite soft magnetic powder. [Figure 4] 13 is a table showing evaluation test results. [Diagram 5] 13 is a table showing evaluation test results. [Figure 6] 13 is a table showing evaluation test results. [Figure 7] 13 is a table showing evaluation test results. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, embodiments of the magnetic core material and the magnetic core according to the present invention will be described.

[0024] The positional relationship of the magnetic core and coil arranged in an induction heating device such as a high-frequency hardening device is shown in Fig. 1 and Fig. 2. As shown in Fig. 1 and Fig. 2, the coil 2 is composed of a pipe or plate made of a conductive metal material such as copper. In order to improve the heating efficiency or adjust the heating area, the magnetic core 1 that controls the magnetic flux is arranged close to the coil 2. This magnetic core 1 can change the state of induction heating by concentrating the magnetic flux generated by the current flowing through the coil 2 on the workpiece or shielding it. Fig. 1 shows a form in which the magnetic core 1 is fitted inside the coil 2, and Fig. 2 shows a form in which the magnetic core 1 is arranged in a part of the winding direction on the outside of the coil 2. In this way, the magnetic core 1 is arranged inside or outside the coil 2 in a form combined with the coil 2.

[0025] The magnetic core 1 is obtained by compression molding a magnetic core material made of composite soft magnetic powder containing resin powder and Fe-based soft magnetic powder, and then heating to harden the resin. As shown in FIG. 3, the composite soft magnetic powder particles 4 have a structure in which an inorganic insulating film 4b is formed on the surface of the Fe-based soft magnetic particles 4a, and an unhardened resin film 4c is further formed on the surface of the inorganic insulating film 4b. The magnetic core 1 is manufactured by compression molding the composite soft magnetic powder 4 together with a solid lubricant, and then thermally hardening the resin film 4c. After that, post-treatments such as cutting, barrel processing, and rust prevention treatment are performed as necessary. The shape of the magnetic core 1 to be placed can be changed as appropriate depending on the shape, size, location, etc. of the high-frequency coil.

[0026] As the Fe-based soft magnetic particles 4a, pure iron powder is preferable, and among them, atomized iron powder, especially water atomized iron powder, is preferable. Water atomized iron powder is an iron powder produced by pulverizing molten steel with high-pressure water, cooling it, and then heat-treating it in a hydrogen atmosphere, and has the characteristic that the particles are solid and generally spherical without any voids. In addition to atomized iron powder, reduced iron powder is also known as iron powder, but reduced iron powder is porous with many voids and has many irregularities on the surface. Since each particle of atomized iron powder is spherical, the specific surface area of ​​the particles can be made smaller than that of reduced iron powder. This makes it possible to reduce the relative permeability of the magnetic core 1. In addition, the thickness of the resin binder between the magnetic powder particles is increased, so that the insulation property can be improved and the volume resistivity can be increased. Furthermore, the corrosion resistance increases due to the increased thickness of the resin binder, so that it can be suitably used as a magnetic core for high-frequency hardening devices used in environments where cooling water is directly applied.

[0027] In addition to using pure iron powder as the Fe-based soft magnetic particles 4a, low-alloy steel powder such as iron-silicon alloy, iron-chromium alloy, iron-silicon-chromium alloy, iron-nitrogen alloy, iron-nickel alloy, iron-carbon alloy, iron-boron alloy, iron-cobalt alloy, iron-phosphorus alloy, iron-nickel-cobalt alloy, and iron-aluminum-silicon alloy (Sendust alloy) can be used. In this case, too, it is preferable that the Fe-based soft magnetic particles 4a are formed from atomized steel powder (particularly water-atomized steel powder).

[0028] As the alloying components of these low alloy steel powders, it is preferable to use either or both of Si and Cr. This low alloy steel powder contains either or both of Si and Cr, with the balance being iron and unavoidable impurities. The total content of the alloying components in the low alloy steel powder is preferably 6.5 mass% or less. If the content of the alloying components is too high, the compressibility is poor, the required magnetic properties cannot be secured, and the processability is also reduced. For example, Fe4.5Si can be used as the Fe-Si alloy, Fe2Cr as the Fe-Cr alloy, and Fe4.5Si2Cr as the Fe-Si-Cr alloy.

[0029] The entire surface of the Fe-based soft magnetic particles 4a is covered with an inorganic insulating coating 4b. As the material of the inorganic insulating coating 4b, it is preferable to use a metal phosphate such as iron phosphate, manganese phosphate, zinc phosphate, calcium phosphate, or aluminum phosphate. In addition, various silane coupling agents may be used. The inorganic insulating coating 4b may be formed of one type of material, or may be formed of two or more types of materials. An example of a commercially available Fe-based soft magnetic powder in which the surface of the Fe-based soft magnetic particles 4a is covered with an inorganic insulating coating 4b is Somaloy, a product manufactured by Höganäs AG.

[0030] From the viewpoint of suppressing heat generation of the core itself, it is preferable to use Fe-based soft magnetic powder with a median diameter D50 (particle diameter at which the cumulative frequency based on the number of particles is 50%) of 10 μm or more and 70 μm or less. If the particle diameter of the Fe-based soft magnetic powder is too small, it becomes difficult to form a resin coating 4c on the surface. If the particle diameter is too large, the iron loss increases. In particular, when pure iron powder is used as the Fe-based soft magnetic particles 4a, it is preferable that the median diameter D50 is 40 μm or more and 70 μm or less, and when low-alloy steel powder is used as the Fe-based soft magnetic particles 4a, the median diameter D50 is 10 μm or more and 30 μm or less.

[0031] The resin coating 4c is made of an epoxy resin material consisting of an epoxy resin and a hardener. The epoxy resin is obtained by mixing a bisphenol A type epoxy resin and a novolac type epoxy resin. The novolac type epoxy resin has three or more functional groups per molecule, and has a property of being easily crosslinked in three dimensions compared to a bisphenol A type epoxy resin having two functional groups per molecule. If only a bisphenol A type epoxy resin is used as the epoxy resin, there is a problem that the epoxy resin material will blow out from the inside onto the surface of the molded body during heat curing, as described below, and the shape of the molded body cannot be maintained. The epoxy resin material is a thermosetting resin that reacts and hardens by heating a combination of a base agent and a hardener, but by raising the temperature, the viscosity of the unreacted part decreases, increasing the fluidity and making it easier to blow out. By adding a novolac type epoxy resin to a bisphenol A type epoxy resin, the viscosity of the epoxy resin increases, and it is possible to prevent the epoxy resin from blowing out during heat curing. As an epoxy resin obtained by mixing bisphenol A type epoxy resin and novolac type epoxy resin, for example, "Epiform EPX-6136" manufactured by Somar Co., Ltd. can be used.

[0032] If novolac epoxy resin is used alone, the strength of the molded body after heat curing may be insufficient. The magnetic core placed in induction heating devices such as high-frequency hardening devices is processed to fit the shape of the workpiece and coil, so it needs to be strong enough to withstand processing.

[0033] A latent epoxy curing agent is used as a component of the curing agent. By using the latent epoxy curing agent, the softening temperature can be set to 100 to 120°C and the curing temperature can be set to 170 to 200°C, making it possible to form an organic insulating coating film (resin coating 4c) on each particle of the Fe-based soft magnetic powder, and then perform compression molding and thermal curing. Examples of latent epoxy curing agents include dicyandiamide, boron trifluoride-amine complex, and organic acid hydrazide. Among these, it is preferable to use dicyandiamide, which meets the above-mentioned effect conditions. A curing accelerator such as a tertiary amine, imidazole, or aromatic amine can be included together with the latent epoxy curing agent.

[0034] The amount of latent hardener contained in the epoxy resin material is determined according to the heating temperature and heating time. For example, the amount of latent hardener is selected so that the epoxy resin is hardened by heating at a heating temperature of 200° C. for 1 hour.

[0035] The amount of epoxy resin material (including hardener) in the magnetic core material, which is the raw material of the magnetic core, is preferably 2 mass% or more and 5 mass% or less, with the remainder being Fe-based soft magnetic powder, inorganic insulating coating, and solid lubricant. If the content of epoxy resin material is less than 2 mass%, it is difficult to form an effective insulating coating, and the strength is reduced. If the content of epoxy resin material is more than 5 mass%, the magnetic properties are reduced, and large resin-rich aggregates are generated. The amount of solid lubricant is preferably about 0.5 mass% to 1 mass%. For example, Kenolube manufactured by Höganäs can be used as the solid lubricant at 0.5 mass%. In addition, metal soap-based and fatty acid amide-based solid lubricants may be used.

[0036] When pure iron powder is used as the Fe-based soft magnetic particles 4a, the amount of epoxy resin is preferably 3 mass% or more and 5 mass% or less. When low-alloy steel powder is used as the Fe-based soft magnetic particles 4a, the amount of epoxy resin is preferably 2 mass% or more and 5 mass% or less.

[0037] In the manufacturing process of the magnetic core according to the present embodiment, the above-mentioned Fe-based soft magnetic powder and the epoxy resin material are dry-mixed at a temperature of 100 to 120°C to form an uncured resin coating 4c on the inorganic insulating coating 4b covering the surface of the Fe-based soft magnetic particles 4a. This uncured resin coating is also an insulating coating, and after thermal curing, a composite insulating coating of the inorganic insulating coating and the resin coating is formed on the surface of the Fe-based soft magnetic particles 4a. This composite insulating coating significantly improves the insulating properties of the coating, so high electrical insulation can be obtained. The above-mentioned raw material (magnetic core material) is supplied to a mold and compressed to form a molded body, which is then thermally cured at a temperature equal to or higher than the thermal curing start temperature of the epoxy resin material to obtain an integrated magnetic core 1.

[0038] The manufacturing method of the magnetic core will now be described in detail. The above-mentioned Fe-based soft magnetic powder and the above-mentioned epoxy resin material in which the latent hardener is already blended are prepared. The Fe-based soft magnetic powder is passed through a classifier in advance to prepare a D50 of 10 to 70 μm.

[0039] Next, in a mixing process, the Fe-based soft magnetic powder and the epoxy resin material are dry-mixed together with a solid lubricant at a temperature equal to or higher than the softening temperature of the epoxy resin and lower than the thermal curing start temperature. In this mixing process, the Fe-based soft magnetic powder and the epoxy resin material are first thoroughly mixed at room temperature using a blender or the like. Next, the mixed mixture is put into a mixer such as a kneader and heated and mixed at the softening temperature of the epoxy resin material (100 to 120°C). Through this heating and mixing process, an insulating coating 4c (see FIG. 3) of the epoxy resin material is formed on the surface of each particle of the Fe-based soft magnetic powder. At this stage, the epoxy resin material is uncured.

[0040] The contents that have been heated and mixed using a mixer such as a kneader are in the form of an aggregated cake. The pulverization process is a process in which the aggregated cake is pulverized at room temperature and sieved to obtain a composite soft magnetic powder having an insulating coating of epoxy resin material formed on the surface. The pulverization is preferably performed using a Henschel mixer, and the sieving is preferably performed to obtain particles that pass through a 60 mesh (250 μm) sieve.

[0041] The mold used in the compression molding step may be one capable of applying a molding pressure of 85 to 294 MPa. If the molding pressure is less than 85 MPa, the magnetic properties and strength are low, and if it exceeds 294 MPa, problems such as the epoxy resin sticking to the inner wall of the mold or the insulation being reduced due to the destruction of the resin coating may occur. When pure iron powder is used as the Fe-based soft magnetic particles 4a, the molding pressure is preferably 85 MPa or more and 150 MPa or less, and when low-alloy steel powder is used as the Fe-based soft magnetic particles 4a, the molding pressure is preferably 98 MPa or more and 245 MPa or less.

[0042] The molded product removed from the mold is heat-cured at a temperature of 170 to 200°C for 45 to 80 minutes. This is because curing takes a long time at temperatures below 170°C, and deterioration begins at temperatures above 200°C. Heat-curing is preferably carried out in a nitrogen atmosphere, but an atmosphere containing oxygen, such as air, may also be used. After heat-curing, cutting, barrel processing, rust prevention treatment, etc. are carried out as necessary to obtain the magnetic core 1 shown in Figures 1 and 2.

[0043] The evaluation tests carried out to evaluate the characteristics of the magnetic core 1 described above will be described below, and the results will be described with reference to Figs. 4 to 7. In addition, Examples 1 to 5 and Comparative Examples 1 to 4 are test pieces in which pure iron powder is used as the Fe-based soft magnetic particles 4a (see Fig. 4), and Examples 6 to 8 and Comparative Example 5 are test pieces in which low-alloy steel powder is used as the Fe-based soft magnetic particles 4a (see Fig. 5). In addition, Examples 1, 4, 5, and Comparative Examples 2 to 4 are test pieces in which the amount of epoxy resin contained is different (see Fig. 4). The types of epoxy resin are different between Examples 1 to 5 and Comparative Example 1, and the molding pressure is different between Examples 1 to 3 (see Fig. 4). In addition, Examples 6 to 8 and Comparative Example 5 are test pieces in which the types and amounts of alloy components contained in the Fe-based soft magnetic particles 4a are different (see Fig. 5). In Figs. 4 and 5, the Fe-based soft magnetic particles 4a (pure iron powder and low-alloy steel powder) are each referred to as "iron powder".

[0044] [Example 1] The test piece of Example 1 is produced by the following procedure. (1) 95 mass% of water-atomized pure iron powder with a phosphate coating, 4.5 mass% of epoxy resin material made by adding dicyandiamide as a hardener to bisphenol A type epoxy resin and novolac type epoxy resin, and 0.5 mass of wax-based lubricant Kenolube (manufactured by Höganäs) as a solid lubricant are mixed in a rocking mixer at room temperature for 10 minutes. The water-atomized iron powder used has a particle size of 40 to 70 μm, with a D50 value determined by number. (2) This mixture is charged into a kneader and kneaded under heat at a heater temperature of 100° C. for 10 minutes using both normal pressure kneading and pressurized kneading. (3) After being charged into the kneader, the agglomerated cake obtained by kneading is broken down and then pulverized in a grinder. (4) After grinding, particles passing through a JIS Z8801-1 (2006) sieve with 30 mesh (500 μm) openings are used as compound powder (raw material powder). (5) Next, the raw material powder is compression molded using a metal mold at a molding pressure of 118 MPa. (6) The compression-molded product is removed from the mold and heated in the air at 200°C for one hour to harden the epoxy resin and produce a toroidal magnetic core.

[0045] [Example 2] The test piece of Example 2 was produced under the same conditions as Example 1, except that the molding pressure condition was changed to 88 MPa.

[0046] [Example 3] The test piece of Example 3 was produced under the same conditions as Example 1, except that the molding pressure condition was changed to 147 MPa.

[0047] [Example 4] In Example 4, compared to Example 1, the amount of iron powder was changed to 96.5 mass %, and the amount of resin was changed to 3 mass %.

[0048] [Example 5] In Example 5, compared to Example 1, the amount of iron powder was changed to 94.5 mass %, and the amount of resin was changed to 5 mass %.

[0049] [Example 6] In Example 6, the iron powder was changed to Fe4.5Si, the insulating coating was changed to a silane coupling agent, the amount of resin was changed to 2 mass%, and the particle size of the iron powder was changed to D50=20 μm, compared to Example 1.

[0050] [Example 7] In Example 7, the iron powder in Example 6 was changed to Fe2Cr.

[0051] [Example 8] In Example 8, the iron powder in Example 6 was changed to Fe4.5Si2Cr.

[0052] [Comparative Example 1] In Comparative Example 1, the epoxy resin used was changed to only bisphenol A type epoxy resin as compared to Example 4. In addition, the kneading conditions were changed to 110° C. for 15 minutes, and the molding pressure was changed to 147 MPa.

[0053] [Comparative Example 2] In Comparative Example 2, unlike Example 1, no epoxy resin was added, the iron powder was changed to 99.5 mass%, and the molding pressure was changed to 196 MPa.

[0054] [Comparative Example 3] In Comparative Example 3, the composition of Example 1 was changed to 98.5 mass % of iron powder and 1.0 mass % of epoxy resin.

[0055] [Comparative Example 4] In Comparative Example 4, compared to Example 1, the iron powder was changed to 92.5 mass % and the epoxy resin was changed to 7.0 mass %.

[0056] [Comparative Example 5] In Comparative Example 5, the iron powder in Example 6 was changed to Fe3.5Si4.5Cr.

[0057] The density, inductance retention, relative permeability, radial crushing strength, and volume resistivity were measured for each of the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 5. The measurement methods for each evaluation item are as follows. When measuring the inductance retention, relative permeability, and volume resistivity, a winding was wound around the magnetic core to provide an inductance of 10 μH.

[0058] "Density" refers to the relative density of the test piece after the epoxy resin is cured. The density was measured in accordance with JIS Z8807:2012.

[0059] The "inductance retention rate" is calculated by using an LCR meter to measure the inductance value when a current of 5 kHz and 1000 kHz is passed through it. The inductance value at 5 kHz is taken as 100%, and the percentage (%) of the inductance value when a current of 1000 kHz is passed through it is the "inductance retention rate". The smaller the inductance retention rate, the worse the frequency characteristics in the high frequency range will be.

[0060] The "relative magnetic permeability" was measured by winding a wire around a ring-shaped magnetic core of φ20.2×φ12.6×t6 (mm) to give an inductance of 10μH, and measuring the initial magnetic permeability at 5kHz, using an LCR meter (5kHz, 10mA, constant current mode) according to the initial magnetic permeability measurement method in accordance with JIS C2560-2:2006. As already mentioned, it is desirable for magnetic cores for induction hardening devices used in high frequency ranges of 100KHz or more to achieve a relative magnetic permeability of 25 or less. The "inductance retention" was measured by winding a wire around a ring-shaped magnetic core of φ20.2×φ12.6×t6 (mm) to give an inductance of 10μH, using an LCR meter (5kHz, 10mA, constant current mode) according to the initial magnetic permeability measurement method in accordance with JIS C2560-2:2006, from 5kHz to 1000kHz.

[0061] "Volume resistivity" was measured according to the measurement method specified in JIS K6911. The smaller the volume resistivity, the greater the eddy current loss, which increases the heat loss in the high frequency range, so a volume resistivity as large as possible is desirable. "Radial crushing strength" was measured according to the provisions of JIS Z2507:2000.

[0062] The test results are shown in Figs. 4 to 7. Figs. 4 and 5 show the measured values ​​for each evaluation item, and Figs. 6 and 7 show the judgment results for each evaluation item. In Figs. 6 and 7, the inductance retention rate was judged as ◯ if it was 80% or more, and x if it was less than 80%. The relative permeability was judged as ◎ if it was 19 or more and less than 23, ◯ if it was 17 or more and less than 19 or 23 or more and 25 or less, and x if it was otherwise. The radial crushing strength was judged as ◎ if it was more than 61, ◯ if it was 50 or more and 60 or less, and x if it was less than 50. The volume resistivity was judged as 10 6 Order more than 10 4 ~10 5 Order 〇, 10 3 Order △, 10 2 Anything below the order was judged as "X." For the overall judgment, if there was even one item with an "X," it was judged as "X," and the rest were judged as "O."

[0063] From the comparison of the measurement results of Example 1, Examples 4 to 8, and Comparative Examples 1 to 4, it can be understood that if a magnetic core is manufactured using a magnetic core material containing Fe-based soft magnetic powder in which an inorganic insulating film is formed on the surface of Fe-based soft magnetic particles, and an epoxy resin material consisting of a hardener and an epoxy resin, the Fe-based soft magnetic particles are pure iron powder or low alloy steel powder, the content of the epoxy resin material is 2 mass% or more and 5 mass% or less, and the epoxy resin is made of bisphenol A type epoxy resin and novolac type epoxy resin, a magnetic core for a high-frequency hardening device can be obtained that has low magnetic permeability (25 or less), good frequency characteristics (high inductance retention rate), and satisfies the required radial crushing strength and volume resistivity. In addition, since no epoxy resin is blown out during heat curing, it is possible to avoid concerns about deterioration of productivity, deviation of the relative magnetic permeability of the molded body from the target value, and deterioration of insulation and strength.

[0064] In contrast, in Comparative Example 1, in which no novolac-type epoxy resin was used, blowing out of the epoxy resin occurred. As a result, it was found that the dimensional accuracy of the molded body was reduced, and the relative magnetic permeability also exceeded the target value (30). In Comparative Example 2, in which no epoxy resin was used, it was found that the relative magnetic permeability exceeded the target value, the strength was lower than the target value, and the volume resistivity was also lower than the target value. In Comparative Example 3, in which the amount of epoxy resin was below the lower limit, it was found that the relative magnetic permeability was high, the strength was weak, and the volume resistivity was also lower than the target value. In Comparative Example 4, in which the amount of epoxy resin was above the upper limit, blowing out of the epoxy resin occurred, and it was found that it was impossible to produce an evaluation sample.

[0065] Furthermore, a comparison of the measurement results of Examples 6 to 8 and Comparative Example 5 revealed that when low-alloy steel powder is used as the Fe-based soft magnetic particles, the relative permeability exceeds the target value when the content of the alloy components exceeds 6.5 mass%. [Explanation of symbols]

[0066] 1 Magnetic core 2 Coil 3 current 4 Composite soft magnetic powder 4a Fe-based soft magnetic particles 4b Inorganic insulating coating

Claims

1. A magnetic core material comprising an Fe-based soft magnetic powder in which an inorganic insulating coating is formed on the surface of an Fe-based soft magnetic particle, an epoxy resin material, and a solid lubricant, the epoxy resin material being made of a hardener and an epoxy resin, The Fe-based soft magnetic particles are pure iron powder or low alloy steel powder, The content of the epoxy resin material is 2 mass% or more and 5 mass% or less, A magnetic core material, characterized in that the epoxy resin comprises a bisphenol A type epoxy resin and a novolac type epoxy resin.

2. 2. The magnetic core material according to claim 1, wherein the Fe-based soft magnetic particles are low-alloy steel powder, the low-alloy steel powder contains either one or both of Si and Cr as alloy components, and the total content of the alloy components in the low-alloy steel powder is 6.5 mass or less.

3. 2. The magnetic core material according to claim 1, wherein the Fe-based soft magnetic particles are pure iron powder, and the content of the epoxy resin material is 3 mass % or more and 5 mass % or less.

4. The magnetic core material according to any one of claims 1 to 3, wherein the Fe-based soft magnetic powder has a median diameter D50 of 10 µm or more and 70 µm or less.

5. A magnetic core formed by curing the epoxy resin of the magnetic core material according to any one of claims 1 to 4.

6. 6. The magnetic core according to claim 5, wherein the relative permeability is 17 to 25.

7. 7. The magnetic core according to claim 5, having a radial crushing strength of 50 MPa or more.

8. Volume resistivity is 1×10 4 The magnetic core according to any one of claims 5 to 7, having a resistivity of Ωcm or more.

9. 9. The magnetic core according to claim 5, wherein the inductance retention rate at 1000 kHz relative to 5 kHz is 80% or more.

10. The magnetic core according to any one of claims 5 to 9, which is arranged in combination with a coil of an induction heating device.

Citation Information

Patent Citations

  • Composition for manufacturing magnetic or magnetized molded articles, and method for manufacturing the composition.

    JP2013522441A

  • Composite magnetic material precursor for magnetic core, composite material for magnetic core, magnetic core, and electronic component

    JP2020167382A

  • Magnetic core and method for manufacturing same

    WO2016043295A1